Concentration of a widespread breeding population in a few critically important nonbreeding areas: Migratory connectivity in the Prothonotary Warbler. (19th June 2019) - Tonra, Christopher M; Hallworth, Michael T; Boves, Than J; Reese, Jessie; Bulluck, Lesley P; Johnson, Matthew; Viverette, Cathy; Percy, Katie; Ames, Elizabeth M; Matthews, Alix; Slevin, Morgan C; Wilson, R Randy; et al.
Abstract: One of the greatest challenges to informed conservation of migratory animals is elucidating spatiotemporal variation in distributions. Without such information, it is impossible to understand full-annual-cycle ecology and effectively implement conservation actions that address where and when populations are most limited. We deployed and recovered light-level geolocators ( n = 34) at 6 breeding sites in North America across the breeding range of a declining long-distance migratory bird, the Prothonotary Warbler ( Protonotaria citrea ). We sought to determine migratory routes, stopover location and duration, and the location of overwintering grounds. We found that the species exhibits a large-scale, east‒west split in migratory routes and weak migratory connectivity across its range. Specifically, almost all individuals, regardless of breeding origin, overlapped in their estimated wintering location in northern Colombia, in an area 20% the size of the breeding range. Additionally, most of the individuals across all breeding locations concentrated in well-defined stopover locations in Central America while en route to Colombia. Although error inherent in light-level geolocation cannot be fully ruled out, surprisingly much of the estimated wintering area included inland areas even though the Prothonotary Warbler is considered a specialist on coastal mangroves in winter. Based on these results, conservation efforts directed at very specific nonbreeding geographical areas will potentially have benefits across most of the breeding population. Our findings highlight the importance of using modern technologies to validate assumptions about little-studied portions of a species' annual cycle, and the need to distribute sampling across its range.